PRODUCTIVITY OF WINTER WHEAT DEPENDING ON PREDECESSORS - I. I. Galichenko (Зерновое хозяйство России)
Winter wheat is the most important food crop in Russia, having significant value in grain production. It uses bioclimatic potential of the regions better and gives stable grain harvests. The basic purpose of the farmers is to get better harvests of winter wheat with high technological properties. The complex of agricultural methods for winter wheat is determined by the predecessor. It influences on soil fertility and on moisture reserves in a root zone. Such scientists as N.N. Borodin (1976), I.G. Kalinenko (1979), V.A. Alabushev (1987), I.I. Galichenko (2011) and others recon that ‘black’ fallow ground gives the highest harvests of winter wheat, as it largely supplies plants with water and nutrients, improves phytosanitary conditions, reduces soil weediness. The tasks of primary importance are to develop and improve optimal technological methods of winter wheat growing with the best predecessors. The problem is to find the best correlation between ‘black’ fallow and cropped fallow that will guarantee to get high productivity of winter wheat. It is established that the best predecessor of winter wheat is weedfree fallow. The productivity of the crop after weedfree fallow was higher on 1,27 t/ha compared with non-fallow predecessors.